Synthesis of gold nanoparticles on carbon nanotubes/anodized aluminium oxide for catalytic reduction of p-nitrophenol / Farah Wahida Ahmad Zulkifli - Ahmad Zulkifli, Farah Wahida (2019)
Gold nanoparticles (Au NPs) have been widely used in various applications specifically in the field of catalysis. Au supported catalyst are more favoured over the homogeneous one since it gives superior features such as simplicity in recovery and regeneration. In this research, Au NPs supported on functionalized carbon nanotubes (Au-fCNT) catalysts were successfully synthesized via deposition-precipitation (DP) as this method was a more efficient and simpler approach.